A systematic review of the knowledge, attitude, and practices (KAP) of food safety among street food handlers - Wan Fatihah, Wan Nawawi; Vimala, Ramoo; Chong, Mei Chan; Khatijah Lim, Abdullah * (Faculty of Food Science & Technology, 2022)
Foodborne diseases are commonly reported from various food establishments; however, little information has been obtained on this topic from the street food industry. Therefore, the present systematic review aimed to provide an overview of the knowledge, attitude, and practices (KAP) of food safety among street food handlers to highlight relevant gaps in the safety and quality of food handling. Articles included in the present systematic review were extracted from several electronic databases based on the PRISMA protocol and CASP checklist. By applying inclusion criteria, twelve peer-reviewed studies from 2010 to 2020 were included in the present systematic review. Results revealed that the food safety KAP level among street food handlers varied across the study settings. It was also found that training plays an essential role in improving food safety practices. KAP assessment is essential as an initial diagnosis to guide and prioritise appropriate strategies based on the food safety aspect that requires the most attention. It also provides a decisionmaking basis for food safety authorities to develop relevant policies, and organise food safety training.